Application of Telemedicine in the Covid-19 Scenario: Technology as Health Care in front of Emergency Crisis - Reckziegel, Janaina; Cobos Campos, Amalia Patricia; Matos Ludwig, Wendell Wesley (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
The objective was to present the main impacts of the application of telemedicine in health service systems and its exercise in the face of containing the spread of the virus. The methodology used was based on bibliographic reviews and quantitative analysis involving studies on the contributions of telemedicine as an exchange of information between health professionals. It is concluded that it is an essential service today, being a potentiating instrument in providing improvements to the development of medicine, overcoming the challenges arising from it.